The use of "mafia capital" in Emilia and Eastern Lombardy. From cultural contiguity to the effects of mafia enterprise. (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The article analyses some aspects of the mafia phenomenon in Mantua, Cremona, Piacenza, and Reggio Emilia – the so-called “quadrilateral of the Po valley” - through a triangulation between qualitative and quantitative methods. It is divided into two parts. The first aimed at investigating the orientations of thoughts and actions, that have facilitated the establishment of the Cutro clans (KR); the second aimed at quantifying the effects of mafia entrepreneurship on the local economy.
Keywords: ’Ndrangheta, mafia taxation, cultural contiguity, triangulation, padan quadrilateral